2019
DOI: 10.1111/bju.14851
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prostate‐specific antigen persistence after radical prostatectomy on the efficacy of salvage radiotherapy in patients with primary N0 prostate cancer

Abstract: Objective To test whether salvage radiotherapy (SRT) in patients with lymph node negative (N0) prostate cancer is equally effective with persistent prostate‐specific antigen (PSA) and PSA rising from the undetectable range (<0.1 ng/mL) after radical prostatectomy (RP). Patients and methods We assessed post‐SRT PSA progression‐free survival (PFS) in 555 patients with prostate cancer. The entire cohort was compared with a risk‐adjusted subgroup of 112 patient pairs with matching pre‐RP PSA level (±10 ng/mL), Gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…We evaluated initial tumor stage [10] (T2c ≤ vs. ≥ T3a), initial nodal status [11] (N0 vs. N1), initial Gleason score [10,11] (7a ≤ vs. ≥ 7b), and initial resection status [11] (R0 vs. R1). Further, we evaluated the risk factors PSA persistence > 0.1 ng/mL after RP [12], PSA level at PMSA-PET imaging/recurrence [10,11], age at relapse as well as the PSMA-PET-related factors local recurrence (no vs. yes), pelvic lymph node lesions (no vs. yes), distant metastases (no vs. yes), and the number of lesions at PSMA-PET imaging. We used receiver operating characteristic (ROC) analysis to determine cutoff values for non-dichotomous variables.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated initial tumor stage [10] (T2c ≤ vs. ≥ T3a), initial nodal status [11] (N0 vs. N1), initial Gleason score [10,11] (7a ≤ vs. ≥ 7b), and initial resection status [11] (R0 vs. R1). Further, we evaluated the risk factors PSA persistence > 0.1 ng/mL after RP [12], PSA level at PMSA-PET imaging/recurrence [10,11], age at relapse as well as the PSMA-PET-related factors local recurrence (no vs. yes), pelvic lymph node lesions (no vs. yes), distant metastases (no vs. yes), and the number of lesions at PSMA-PET imaging. We used receiver operating characteristic (ROC) analysis to determine cutoff values for non-dichotomous variables.…”
Section: Discussionmentioning
confidence: 99%
“…In 14 retrospective studies comparing the oncologic outcomes between patients having or not having an undetectable PSA value after RP, PSA persistence was significantly correlated with poorer survival rates, according to the endpoint used (BCRFS, MFS, CSS, or OS). PSA persistence was not an independent predictive factor for BCRFS in only two studies in which all patients were treated by sRT [12,15]. Gandaglia et al [23] suggested that the impact of PSA persistence on outcomes might be influenced by the overall risk of CSM.…”
Section: Follow-upmentioning
confidence: 97%
“…In comparative studies and RCTs, the proportion of patients with detectable versus those achieving an undetectable value ranged from 3.1% to 54.2% according to the selection criteria. Five studies included only patients receiving sRT [1,12,15,17,19,24]. Patients having positive lymph nodes at final pathology (pN1 disease) were excluded from analysis in six retrospective studies and five RCTs [1,12,17,19,21,24].…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In their retrospective study, Bartkowiak et al. report the therapeutic outcomes of salvage radiation therapy (sRT) after radical prostatectomy (RP) for lymph‐node‐negative prostate cancer in 422 and 133 patients with biochemical relapse or persistently detectable PSA, respectively. In the total cohort, patients with persistent PSA serum levels ≥0.1 ng/mL postoperatively had significantly shorter progression‐free survival as compared to patients with undetectable PSA levels ( P < 0.001).…”
mentioning
confidence: 99%